Effective teacher training : cooperative learning based approach - Zangira, En. Ke; Ahuja, Anupam (New Delhi, India : National, 1992)
Study in the Indian context
Includes index
Includes bibliographical references
Keywords: Teachers -- Training of -- India; Education